CFD analysis and geometrical parameter investigation for the design of a high-efficiency supersonic ejector - Elgezzar M.; Rashad A.; Hassan M.S.; Elnady T. (FME Transactions, 2024)
This paper presents a CFD analysis of a supersonic ejector model for refrigeration systems. The model is validated by comparing it with previous studies and used to design a high-efficiency ejector. The effects of geometrical parameters such as convergence angle, throat length, divergence angle, and diffuser length on the entrainment ratio are studied. The optimal values of these parameters are found and used to modify the base model. The performance of the optimized model is evaluated under different operating conditions. The paper aims to provide design guidelines for supersonic ejectors in refrigeration applications.